(untitled) (Medico Legal Update, 2021)
The aims of our study were to investigate association of some effect of pro- inflammatory and antiinflammatory cytokines before and after surgical patients through study serum concentration of, TNF-?, IL-2, IL-4, IL-6, IL-10. 35 blood samples were collected from surgical patients (17 male, 18 female)with general anesthesia from Al-Diwaniyah Hospital, Iraq. Samples were taken before surgery (Tpre), the first day) T1), third day) T3 (and fifth day (T5) after operative after skin incision.Pro-inflammatory cytokines (IL-2, IL-6, and TNF-?) and anti-inflammatory cytokines (IL-4, IL-10) were quantitatively analyzed by ELISA technique.Our resultsshowed there were no significant difference (p<0.05) in WBCs count, WBCs percentage (neutrophil, eosinophil, basophil, monocytes and lymphocytes), PCV, PCT percentage and HB concentration before (Tpre) and after (T1, T3, and T5) surgical operation. Also the results showed there were a significant decrease in IL-2 concentration in (T1) and (T3) day postoperative surgery compared with (T pre), and returned to the pre-operative values on (T5). IL-6 showed significant increase in first day postoperative (T1), and then decreased the (T3 and T5) compared to the (Tpre), TNF? slightly increased in (T1 and T5) but the difference didn’t significantly, IL-4 didn’t show any significant difference between Tpre, T1, T3 and T5. IL-10 showed a significant increase in (T1) compared with (Tpre), and returned to the preoperative values on (T3) and (T5). We could be concludethe pro? and anti?inflammatory cytokines balanced ratio is essential to regulate the inflammatory responses postoperative. Anti-inflammatory cytokine (IL-10) increased in first day postoperative to suppress excessive effect of pro-inflammatory cytokine (IL-6).